ANALISIS KONTRASTIF NOMINALISASI DALAM BAHASA INGGRIS, BAHASA INDONESIA, DAN BAHASA JAWA - Ikmi Nur Oktavianti; Noor Chaerani; Icuk Prayogi (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2019)
Along with verbs, nouns are very crucial—among other lexical and functional categories—in arranging linguistic constructions. Thus, there are many ways to change words from other word classes into nouns or known as nominalization. This paper aims at describing the similarities and differences of nominalization in English, Indonesian, and Javanese. By contrasting three different languages, this study can give another insight on nominalization, especially for language teachers and students of language. This study employed a qualitative method in accordance with the type of data collected (i.e. clauses containing nominalized units). The data were collected using metode simak for English language data and researchers’ intuition as the native speakers of Indonesian and Javanese. English language data were collected from English grammar books. The approach used is contrastive analysis to compare three languages under study. The method of analysis is metode padan translational and metode agih. The results of the analysis show that generally, these three languages use affixation, particles, and conversion as the nominalizers. English, however, differs from Indonesian and Javanese since it doesn’t have reduplication as nominalizer and the use of particle is limited to the initial position. Unlike English, Indonesian and Javanese tend to be alike and it is plausible since both are from the same language family. In the comparison, it is figured out that there are three main similarities and six differences of the realizations of nominalization in English, Indonesian, and Javanese. The results are plausible due to the unrelatedness of English with Indonesian and Javanese.